Let's explore Pluto and other dwarf planets - Orme, Helen; Orme, David, 1948 Mar. 1- (Tunbridge Wells, Kent : Ticktock Entertainment, 2007)
Photographs, illustrations, and simple text provide details about Pluto including what it looks like, its change in classification from planet to dwarf planet, and objects found in Pluto's orbit.
Where is Pluto? -- The outer solar system -- Pluto : a dwarf planet -- Dwarf planet facts -- What's the weather like? -- Pluto's moons -- The Kuiper Belt -- The history of Pluto -- What can we see? -- The New Horizons mission.
Includes index.
3-6.
Keywords: Pluto (Dwarf planet) -- Juvenile literature; Pluto (Dwarf planet); Pluto (Dwarf planet)